Optimization and characterization of electroless co-deposited PdRu membranes: Effect of the plating variables on morphology - Braun, Fernando (2011)
PdRu films were successfully synthesized on top of non-porous stainless steel supports by electroless co-deposition. The effect of synthesis variables on morphology, substrate adherence, bulk and surface composition was studied. The microstructure and morphology of the samples were analyzed by X-ray diffraction and scanning electron microscopy. Homogeneous and defect-free PdRu films were obtained employing baths at low pH, moderate to high agitation speeds, high concentration of hydrazine, using EDTA as a stabilizer and temperatures near 50°C. Films characterized by X-ray photoelectron spectroscopy showed Pd segregation after annealing the sample at 400°C in H2 (5%)/Ar in the load-lock chamber of the spectrometer. The optimized conditions were employed to synthesize a PdRu composite membrane on top of a tubular porous stainless steel substrate (0.1μm grade). Hydrogen permeation was measured over a 350-450°C temperature range and a trans-membrane pressure up to 100kPa. The PdRu membrane showed good performance with a hydrogen permeability of 6.5×10-9molm-1s-1Pa-0.5 and a selectivity higher than 1700.